The dual role of glucocorticoid regeneration in inflammation at parturition - Ling, Li-Jun; Zhou, Qiong; Zhang, Fan; Lei, Wen-Jia; Li, Meng-Die; Lu, Jiang-Wen; Wang, Wang-Sheng; Sun, Kang; Ying, Hao (Frontiers in Immunology, 2024)
Fetal membrane inflammation is an integral event of parturition. However, excessive pro-inflammatory cytokines can impose threats to the fetus. Coincidentally, the fetal membranes express abundant 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1), which generates biologically active cortisol to promote labor through induction of prostaglandin synthesis. Given the well-recognized anti-inflammatory actions of glucocorticoids, we hypothesized that cortisol regenerated in the fetal membranes might be engaged in restraining fetus-hazardous pro-inflammatory cytokine production for the safety of the fetus, while reserving pro-labor effect on prostaglandin synthesis to ensure safe delivery of the fetus. The hypothesis was examined in human amnion tissue and cultured primary human amnion fibroblasts as well as a mouse model. 11β-HSD1 was significantly increased in the human amnion in infection-induced preterm birth. Studies in human amnion fibroblasts showed that lipopolysaccharide (LPS) induced 11β-HSD1 expression synergistically with cortisol. Cortisol completely blocked NF-κB-mediated pro-inflammatory cytokine expression by LPS, but STAT3-mediated cyclooxygenase 2 expression, a crucial prostaglandin synthetic enzyme, remained. Further studies in pregnant mice showed that corticosterone did not delay LPSinduced preterm birth, but alleviated LPS-induced fetal organ damages, along with increased 11β-HSD1, cyclooxygenase 2, and decreased pro-inflammatory cytokine in the fetal membranes. There is a feed-forward cortisol regeneration in the fetal membranes in infection, and cortisol regenerated restrains pro-inflammatory cytokine expression, while reserves prolabor effect on prostaglandin synthesis. This dual role of cortisol regeneration can prevent excessive pro-inflammatory cytokine production, while ensure in-time delivery for the safety of the fetus.